(3QSGdI aj GdYed HGdQHY GdeQShe HGdebfWQGJs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI ai GdYed HGdQHY GdehShe HGdebfWQGJ , hVYJgG deHJOF WQjbkG ddhUhd s
(3BNQgG (B:s
(3hgcPG GdaYd aWGdY WdhYg heWGdY ZQhHg JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B62 - (3U(B66s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
Keywords: (3Gdadcs